Clinical, Radiological and Patient Reported Outcomes of Charcot Foot Reconstructive Surgery in a Single Centre over a Follow Up Period of 1-7 Years - Rebecca Martin MRCS MB BCh BAO; Helena Sylvester MRCS; Jayasree R. Ramaskandhan MSc, PhD; Simon Chambers MBBS, BSc, FRCS (Tr&Orth); Sultan Qasim MBBS, BSc, FRCS (Tr&Orth) (Foot & Ankle Orthopaedics)
Category: Diabetes; Other Introduction/Purpose: The diabetic foot is a major public health issue within the UK and Charcot foot deformity is a possible and challenging consequence to manage. Without treatment patients often suffer from joint instability and recurrent ulceration with possible associated infections. Surgical management of Charcot joint deformity has become a recent but important treatment. In our centre, a hybrid type fixation technique is utilised: internal fixation (plates and beaming techniques) and external fixation (circular frame). The aim is fusion beyond the zone of injury, satisfactory correction of the Charcot deformity and protection of soft tissue envelopes and maintenance of function. The aim of this study was to assess the clinical, radiological and patient reported outcomes for all patients who underwent this hybrid technique of Charcot joint reconstruction. Methods: This is a prospective observational case series of all patients who underwent surgical reconstruction of Charcot foot deformity performed under 2 consultant foot and ankle surgeons in a single centre. The duration of the study included patients operated on between 2017 to 2023 and no patients were excluded. Patient demographics, smoking status, diabetic control and BMI were recorded. Outcomes were determined from case notes and included clinical outcomes (complications, return to theatre, amputation and mortality) radiological outcomes and patient reported outcomes (MOX-FQ scores, EQ-5D and FAOS outcome scores). The follow up period was 1-7 years post operatively. Results: 44 Charcot joint reconstructions were included with operations occurring between 2017 and 2023. The mean age at the time of operation was 59.1 years (range 29 - 91 years). 25 patients were male (56.8%) and 19 were female (43.2%). There were 4 procedures with internal fixation alone (9.1%), 9 procedures with external fixation alone (20.5%) and 31 with a combination of internal and external fixation (70.5%). At the time of most recent follow up, 7 patients were deceased (16.7%) and 2 patients had major amputation on the ipsilateral side. We aim to present the rate of post-operative complications, return to theatre, radiographic outcomes and patient reported outcomes as well as the patients status at time of operation including their glucose control, smoking status and BMI. Conclusion: A hybrid type fixation with combined internal and external fixation is a viable option for patients undergoing Charcot joint reconstruction but the re-operation rate is not negligible and, although the majority of patients had no related issues, complications can occur due to the complex nature of the patient population undergoing these procedures. Patients PROMs scores improved between pre-operative scores and post-operative scores significantly. To best confirm our findings and determine which patients have the best post operative prognosis from these procedures a larger multi-centre study is required.